Inverse problem for a parabolic equation with strong power degeneration - Ivanchov, N. I.; Saldina, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We consider the inverse problem of determining the time-dependent coefficient of the leading derivative in a full parabolic equation under the assumption that this coefficient is equal to zero at the initial moment of time. We establish conditions for the existence and uniqueness of a classical solution of the problem under consideration.